1993
DOI: 10.1080/00914039308012074
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Amorphous Phase of Polyethylene upon High Extension

Abstract: The structure of noncrystalline regions of HDPE oriented filaments prepared by two different techniques with various degrees of orientation X has been studied by density measurements, small-angle X-ray scattering and DTA. It is shown that at A > 10 the noncrystalline regions of the oriented structure prepared from a crystallized material have 80 nrn voids (pores) in addition to an amorphous phase. The volume fraction of pores grows with increasing A. If a sample is prepared by crystallization from apre-oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The increase in flexural modulus for composite in this study was not unanticipated, because such an increase has been reported in the polymer literature 46–48. The increase in modulus in the amorphous regions of polyethylene has been attributed to realignment of the polymer chains along the extension axis at low extension rates 46.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The increase in flexural modulus for composite in this study was not unanticipated, because such an increase has been reported in the polymer literature 46–48. The increase in modulus in the amorphous regions of polyethylene has been attributed to realignment of the polymer chains along the extension axis at low extension rates 46.…”
Section: Discussionsupporting
confidence: 65%
“…A slight increase in tensile strength has been reported to occur with uniaxial extension of polyethylene46 and in natural and synthetic rubbers 50. The increase in strength, as with modulus, has been attributed to chain realignment along the extension axis at low extension rates in the amorphous regions of polyethylene46 and crystallization in natural and synthetic rubbers 50. Not surprisingly, just as with the dentin fatigue studies, the results of this study are not supported by previous composite fatigue studies, which report a decreased fatigue life with increasing loading cycles and indirectly, decreased strength 19, 20.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations